HUMAS DALAM STRATEGI KAMPANYE PARTAI POLITIK - Dede Apriyanti (Cakrawala - Jurnal Humaniora, 2009)
The existence of an ideal political party to activate and mobilise people, representing certain interests, a compromise of concurrent views and provide facilities for the succession of political leadership is legitimate and peace, the party also served to rational and effective link between individuals and the political system, and change the individual becomes a citizen and political system becomes a good government. PR is an important part in partisan politics, this is because political parties require support from the community in general. To gain support in the elections, then the PR carried out various activities to support the achievement of the objectives and voice to win elections. Regarding efforts to mobilize support in the vote of the party in the necessary electoral campaign strategy which can be maximum by their public relations.Keywords: Public Relations, Campaigns, Political Parties.